Macromolecular crowding and decellularization method increase the growth factor binding potential of cell-secreted extracellular matrices - Fok, Shierly W.; Gresham, Robert C. H.; Ryan, Weston; Osipov, Benjamin; Bahney, Chelsea; Leach, J. Kent (Frontiers in Bioengineering and Biotechnology, 2023)
Recombinant growth factors are used in tissue engineering to stimulate cell proliferation, migration, and differentiation. Conventional methods of growth factor delivery for therapeutic applications employ large amounts of these bioactive cues. Effective, localized growth factor release is essential to reduce the required dose and potential deleterious effects. The endogenous extracellular matrix (ECM) sequesters native growth factors through its negatively charged sulfated glycosaminoglycans. Mesenchymal stromal cells secrete an instructive extracellular matrix that can be tuned by varying culture and decellularization methods. In this study, mesenchymal stromal cell-secreted extracellular matrix was modified using λ-carrageenan as a macromolecular crowding (MMC) agent and decellularized with DNase as an alternative to previous decellularized extracellular matrices (dECM) to improve growth factor retention. Macromolecular crowding decellularized extracellular matrix contained 7.7-fold more sulfated glycosaminoglycans and 11.7-fold more total protein than decellularized extracellular matrix, with no significant difference in residual DNA. Endogenous BMP-2 was retained in macromolecular crowding decellularized extracellular matrix, whereas BMP-2 was not detected in other extracellular matrices. When implanted in a murine muscle pouch, we observed increased mineralized tissue formation with BMP-2-adsorbed macromolecular crowding decellularized extracellular matrix in vivo compared to conventional decellularized extracellular matrix. This study demonstrates the importance of decellularization method to retain endogenous sulfated glycosaminoglycans in decellularized extracellular matrix and highlights the utility of macromolecular crowding to upregulate sulfated glycosaminoglycan content. This platform has the potential to aid in the delivery of lower doses of BMP-2 or other heparin-binding growth factors in a tunable manner.